(untitled) (Al-Mansour Journal, 2025)
Water shortage has been a significant issue in arid and semi-arid areas owing to the uneven rainfall distribution, population explosion, and mounting pressure on the traditional water resources. Centralized rainwater harvesting (RWH) systems represent a technically feasible and sustainable approach for augmenting water resources; however, their effectiveness largely depends on the careful selection of suitable locations. Accordingly, this study proposes a GIS-driven decision-support model that integrates DEM-derived hydrological indices with an objective multi-criteria decision-making (MCDM) framework to identify suitable sites for the implementation of centralized RWH systems in Karbala Province, Iraq. Based on Shuttle Radar Topography Mission (SRTM) data, and spatial analysis, six physically meaningful criteria were obtained, namely mean slope, mean elevation, mean curvature, mean log-transformed flow accumulation, mean distance to streams, and site area. To reduce subjectivity, the Entropy Weight Method (EWM) was used to find the relative significance of each criterion objectively. Technique of Order of Preference by Similarity to an Ideal Solution (TOPSIS) was used to rank 23 candidate sites according to their proximity to the ideal solution. The findings indicate that site area and flow accumulation account for the largest share of influence on site suitability, whereas elevation and curvature contribute a comparatively smaller proportion to the overall assessment.